2020
DOI: 10.1002/jcp.30160
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neuropathy target esterase in pre‐eclampsia suppresses tube formation of HUVECs via dysregulation of phospholipid metabolism

Abstract: Recently, studies have shown that neuropathy target esterase (NTE) is essential to placental and normal blood vessel development. However, whether it is involved in abnormal placenta angiogenesis of pre-eclampsia remains unknown. Thus, our aim was to observe the expression of NTE in pre-eclamptic placentas and its effects and mechanism of NTE on the migration and the tube formation of human umbilical vein endothelial cells (HUVECs). Immunohistochemical staining showed that the NTE protein was intensely located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Pnpla6 silencing significantly alters the formation of the respiratory tube and nervous system (Winrow et al, 2003 ) and impairs vasculogenesis and placental vasculature in a mouse model (Moser et al, 2004 ). PNPLA6 overexpression significantly promotes the migration and tube formation of human umbilical vein endothelial cells (HUVECs) (Li et al, 2021 ), and PNPLA6 short hairpin RNA (shRNA) inhibits the migration and tube formation of HUVECs (Li et al, 2021 ). In the current study, the results showed that the level of PNPLA6 expression was much lower in patients with IA than in the controls possibly because of the lower PNPLA6 expression in patients with IA than in the controls, consequently, the risk of angiogenic lesions increases.…”
Section: Discussionmentioning
confidence: 99%
“…Pnpla6 silencing significantly alters the formation of the respiratory tube and nervous system (Winrow et al, 2003 ) and impairs vasculogenesis and placental vasculature in a mouse model (Moser et al, 2004 ). PNPLA6 overexpression significantly promotes the migration and tube formation of human umbilical vein endothelial cells (HUVECs) (Li et al, 2021 ), and PNPLA6 short hairpin RNA (shRNA) inhibits the migration and tube formation of HUVECs (Li et al, 2021 ). In the current study, the results showed that the level of PNPLA6 expression was much lower in patients with IA than in the controls possibly because of the lower PNPLA6 expression in patients with IA than in the controls, consequently, the risk of angiogenic lesions increases.…”
Section: Discussionmentioning
confidence: 99%